Obstacles To The Application Of Electronic Management In Iraqi Universities - Ibrahim Qanbar, Moataz; Jawad Abbas, Kadhim Ahmed (Opción, 2019)
This study aimed to investigate the technical obstacles that face the applica- tion of electronic management at Takrit University, and to discover the organ- izational and human problems, all this from the Administrative and Academic Leadership point of view, and to reach the findings that help in improving the practice of electronic management at the university properly. The researcher used the descriptive method, and questionnaire as a tool, and the researcher applied the tool on (108) persons from Administrative and Academic Lead- ership at Tikrit University as a study society. The results indicated that the average of the areas of obstacles used in this research is ranked according to the mean, First: the radar obstacles and the mean 3.38, second: human obsta- cles and the mean 3.24, finally, technical obstacles reached an average of 3.14. The study showed statistically significant differences between the responses of members of the study community to the obstacles of applying the electronic management due to the variable of scientific qualification in favor of holders of master’s and doctorate qualifications towards the obstacles of applying the academic management.